Dynamic Microbial Shifts and Signatures of Long-Term Remission in Allergic Rhinitis After an Herbal Formula Treatment - Zhu, Libing; Wu, Yuning; Lin, Chenglong; Tang, Lin; Yu, Bin; Wan, Wenrong; Xuan, Jingxiu; Du, Yanling; Chen, Zhangran; Liang, Wei (Frontiers in Immunology, 2021)
A mixed Chinese herbal formula, Xiao-Qing-Long-Decoction (XQLD) may contribute to sustained remission in allergic rhinitis (AR), but it is unknown which factors determine such long-term effect. Here, we aimed to identify bacterial signatures associated with sustained remission. To this end, samples from AR patients at four different time were analysed to compare the dynamic bacterial community and structure shifts. Diversity indices Chao1 showed significant difference across different time (p<0.05) and the Kruskal-Wallis test identified that Dialister (OTU_31), Roseburia (OTU_36), Bacteroides (OTU_22), Bacteroides (OTU_2040) and Prevotella_9 (OTU_5) were the significant differential bacterial taxa (p<0.05). These distinctive genera were significantly associated with the change of AR clinical indices and the predicted functional pathways such as PPAR signaling pathway, peroxisome, and citrate cycle (TCA cycle) (p<0.05), indicating that they may be important bacterial signatures involving in the sustained remission in AR (p<0.05). Besides, lower Firmicutes/Bacteroidetes (F/B) ratio at 6 months follow-up may also contribute to the long-term remission of AR. No seriously adverse events and safety concerns were observed in this study. In conclusion, XQLD is a meaningful, long-term efficient and safe medication for AR treatment. The underlying mechanisms of sustained remission in AR after XQLD treatment may be associated with the dynamic alteration of featured gut bacteria taxa.